2016
DOI: 10.5897/jssem2016.0574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of land management practices on soil physical and chemical properties in Gojeb Sub-river Basin of Dedo District, Southwest Ethiopia

Abstract: This study was undertaken to evaluate the effect of cultivation, fallow and woody land with and without soil bund on soil physical and chemical properties in Gojeb river basin of Dedo district. Landscape of the basin was divided in to three slope positions as upper (25 to 35%), middle (15 to 25%) and lower (5 to 15%). From each slope position, purposely three land use types (cultivated, fallow and woody) lands conserved with and without soil bund were selected. Accordingly, a total of 54 composited soil sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 17 publications
(11 reference statements)
2
9
0
Order By: Relevance
“…e reason might be due to presence of slight increase in amount of clay mineral and OM under conserved farmlands as a result of some deposition. is result was in line with the study conducted by Behailu et al [57] who reported that cultivated lands conserved with soil bund showed higher value of CEC than unconserved under three slope positions.…”
Section: Cation Exchange Capacity (Cec)supporting
confidence: 92%
See 1 more Smart Citation
“…e reason might be due to presence of slight increase in amount of clay mineral and OM under conserved farmlands as a result of some deposition. is result was in line with the study conducted by Behailu et al [57] who reported that cultivated lands conserved with soil bund showed higher value of CEC than unconserved under three slope positions.…”
Section: Cation Exchange Capacity (Cec)supporting
confidence: 92%
“…is is because that cultivated lands with physical soil and water conservation practice might have reduced soil erosion and leaching of exchangeable cations. e result was in line with that of the study conducted by Behailu et al [57] who revealed that cultivated lands treated with soil bund showed higher value of exchangeable Ca 2+ than unconserved one under higher, middle, and lower slope classes.…”
Section: Exchangeable Basessupporting
confidence: 92%
“…The result of the silt content was in agreement with Mengistu et al (2016) who showed higher silt content in nonconserved areas than conserved lands. However, Bezabih, Aticho, and Mossisa (2016) reported higher mean silt content in forestland use compared with agricultural land use. As can be seen in Figure 9, rangelands have the lowest amount of fine particles compared to other land uses, especially to the dam shore, due to transporting the fine soil particles by runoff and rainfall from this area located in the upper catchments to the lower catchments (agricultural lands and dam shore).…”
Section: Relationships Between T-value and Soil Propertiesmentioning
confidence: 88%
“…This seems to be the result of leaching of calcium carbonate in less stable soil conditions, causing a neutral or slightly acidic reaction of the soil (Gunal and Ransom 2006;Rubio and Escudero 2005;Scheatzl and Anderson 2005). However, in the case of heterogeneous soils located on slopes, the loss of carbonates from soil by leaching (decarbonation) is sometimes doubtful (Alijani and Sarmadian 2014;Badía et al 2013). Thus, different causes leading to carbonate removal should be emphasized.…”
Section: The Relations Between Layering Of Slope Deposits and Calciummentioning
confidence: 99%
“…Even if the soils had a high content of calcium carbonate in the entire profile at the beginning of their formation, slope processes (e.g. soil washing, mixing) could lead to depletion or loss of calcium carbonate from the soil material (Alijani and Sarmadian 2014). As the result, the calcium carbonate was preserved in horizons that were not under strong redeposition processes (Kowalska et al 2019).…”
Section: The Relations Between Layering Of Slope Deposits and Calciummentioning
confidence: 99%